On the strong and $Δ$-convergence theorems for total asymptotically nonexpansive mappings on CAT(0) space - Basarir, M.; Şahin, A. (Carpathian Mathematical Publications, 2013)
In this paper, we give the strong and $Δ$-convergence theorems of the modified $S$-iteration and the modified two-step iteration processes for total asymptotically nonexpansive mappings on a CAT(0) space. Our results extend and improve the corresponding recent results announced by many authors in the literature.